Overtourism after the COVID-19 pandemic: Ecological degradation and social tensions in tourist destinations - Femi Diah (Environment Conflict, 2025)
Background: Bali, one of the most popular tourist destinations in the world, has experienced a surge in visitor numbers following the COVID-19 pandemic. While tourism has significantly contributed to the recovery of the local economy, overtourism has emerged as a phenomenon that is causing various environmental and social problems. One of the issues caused by tourism in Bali is the increase in land and property rental prices, as well as the transformation and utilisation of traditional spaces for commercial purposes. This shift not only displaces local communities but also threatens the cultural heritage that makes Bali unique, prompting calls for more sustainable tourism practices that prioritize both the environment and the well-being of residents. Methods: The scope of this research is Bali, especially in the south Bali region, which has been reported to experience overtourism after recovering from the COVID-19 pandemic. This research uses secondary data from published research and other sources, as well as interviews with policymakers, local residents, and related institutions. Findings: This paper aims to analyse environmental degradation and social problems caused by overtourism, especially after the COVID-19 pandemic. The decline in environmental quality has raised concerns among local communities and conservation activists. Furthermore, the social fabric of the region has been strained, as the increasing number of visitors has contributed to increased competition for resources and changed the traditional way of life for many residents. Conclusion: Overtourism in Bali post-pandemic has led to environmental degradation and social disruptions. Sustainable tourism practices are needed to balance economic benefits with the preservation of local communities and cultural heritage. Novelty/Originality of this article: This study highlights the impact of overtourism in Bali after the COVID-19 pandemic, integrating environmental and social perspectives. By using secondary data and interviews with key stakeholders, it provides insights into the urgent need for sustainable tourism strategies.